Green Entrepreneurial Intention in the Context of Global Climate Change Challenges: Strategies for Overcoming Obstacles Through a Learning Environment - Poy Saefullah Zevender; Eeng Ahman; Hari Mulyadi; Kurjono; B. Lena Nuryanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Environmental and social issues have become a major concern in entrepreneurial activities. The low level of green entrepreneurial intention is driven by a lack of institutional support and the public's limited awareness of environmentally friendly products, procedures, and services. This study aims to analyze the moderating effect of the learning environment on the relationships among entrepreneurship learning, student creativity, and green entrepreneurial intention. The method used in this study is an explanatory survey, with a sample of 179 students from the Pangeran Dharma Kusuma Institute in Indramayu. The instrument used was a Likert-scale questionnaire with both positive and negative statements. The data analysis technique used was Multiple Regression Analysis with Moderate Regression Analysis (MRA) in SPSS 26. Entrepreneurship learning and student creativity influence green entrepreneurial intention by 83.6%. Partially, the influence of entrepreneurship learning on green entrepreneurial intention is 78.7% and the influence of student creativity on green entrepreneurial intention is 78.8%. The inclusion of the learning environment moderator variable in each model is 3.2% and 3.5%, respectively. The moderating effects in each model show influences of 3.6% and 0.5%. The implications of this research are expected to make a significant contribution to the literature on green entrepreneurial intentions.